2009
DOI: 10.1074/jbc.m109.014308
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific Deletion of the Growth Hormone Receptor Reveals Essential Role of Growth Hormone Signaling in Hepatic Lipid Metabolism

Abstract: Growth hormone (GH) plays a pivotal role in growth and metabolism, with growth promotion mostly attributed to generation of insulin-like growth factor I (IGF-I) in liver or at local sites of GH action, whereas the metabolic effects of GH are considered to be intrinsic to GH itself. To distinguish the effects of GH from those of IGF-I, we developed a Cre-lox-mediated model of tissue-specific deletion of the growth hormone receptor (GHR). Near total deletion of the GHR in liver (GHRLD) had no effect on total bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
209
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(227 citation statements)
references
References 30 publications
13
209
4
1
Order By: Relevance
“…95) between the two measurements in the combined data are consistent with the above observations. Just as circulating (liver-derived) IGF1 is extracted by the kidney (D'Ercole et al 1984, Kimura et al 1994) and appears to induce gene expression of renal growth factors (Fan et al 2009), it is possible that CNP plays a similar role in the immature kidney. While contributions of CNPs from the kidney and other non-skeletal tissues to circulating levels are likely, our current observations support previous findings of a positive venoarterial CNP gradient across bone dense tissues ) and the correlation of NTproCNP with linear growth velocity in a wide variety of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…95) between the two measurements in the combined data are consistent with the above observations. Just as circulating (liver-derived) IGF1 is extracted by the kidney (D'Ercole et al 1984, Kimura et al 1994) and appears to induce gene expression of renal growth factors (Fan et al 2009), it is possible that CNP plays a similar role in the immature kidney. While contributions of CNPs from the kidney and other non-skeletal tissues to circulating levels are likely, our current observations support previous findings of a positive venoarterial CNP gradient across bone dense tissues ) and the correlation of NTproCNP with linear growth velocity in a wide variety of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that DLK1-overexpressing mice had elevated production of pituitary growth hormone due to a local defect in IGF1 feedback. Because impaired GH signaling is known to cause steatosis by affecting pathways of hepatic lipid import and synthesis (3)(4)(5), as well affecting peripheral FA oxidation (22), we propose that increased dosage of DLK1 acts primarily on the GH axis to shift the metabolic mode toward FA oxidation, with overall beneficial effects on hepatic lipid deposition.…”
Section: Significancementioning
confidence: 99%
“…Depletion of hepatic GH signaling is thought to cause accumulation of triglycerides in the liver in two ways. Firstly, ablation of GH signaling in the liver itself prevents suppression of the fatty acid translocase Cd36, and Pparγ, resulting in increased FA import and biosynthesis (3)(4)(5). Secondly, ablation of GHstimulated hepatic IGF1 release causes elevated circulating GH that induces expression of adipose tissue lipases, adipose tissue lipid mobilization, and lipid flux to the liver (5).…”
Section: Elevated Dlk1 Protects Against High Fat Diet-induced Steatosmentioning
confidence: 99%
See 1 more Smart Citation
“…1F). To determine the effect of APOC3 on hepatic VLDL-TG production, we determined hepatic VLDL-TG production in APOC3-tg versus WT mice, using tyloxapol to inhibit systemic TG clearance, as described (45,46). APOC3-tg mice had significantly higher plasma TG levels at all time points after tyloxapol administration (Fig.…”
Section: Effect Of Apoc3 On the Pathogenesis Of Nafld In Apoc3-tgmentioning
confidence: 99%